Наближення (ψ, β)-диференційовних функцій інтегралами Вейєрштрасса - Харкевич, Ю.I.; Кальчук, I.В. (Український математичний журнал, 2007)
Получены асимптотические равенства для верхних граней приближений функций из классов Cψβ∞ и Lψβ1 интегралами Вейєрштрасса. Asymptotic equalities are obtained for upper bounds of approximations of functions from the classes
C
ψ
β,∞ and L
ψ
β,1
by the Weierstrass integrals.